INTERPROFESSIONAL COLLABORATION FORYOUTH DEVELOPMENT THROUGH SPORT, EXERCISE,AND PHYSICAL EDUCATION - - Caly Setiawan (Jurnal Pendidikan Jasmani Indonesia, 2006)
Tulisan ini bertujuan untuk menstimulasi suatu diskusi tentang kolaborasi interprofesiuntuk pembinaan pemuda melalui program olahraga, latihan, dan pendidikan jasmanidalam konteks kemitraan sekolah-keluarga-komunitas. Sebagai pembuka, artikel inidimulai dengan paparan singkat asumsi kunci tentang kolaborasi. Kemudian, paparantersebut diikuti oleh bagaimana munghubungkan kemitraan antara sekolah-keluargakomunitasyang memampukan integrasi pelayanan. Artikel ini juga menekankan inovasiyang melibatkan pembahasan tentang hambatan dan fasilitator. Bagian akhir dari tulisanini mengidentifikasi implikasi kebijakan ataupun praktis.Kata Kunci: Interprofessional Collaboration, Youth Development, Sport, Exercise, andPhysical Education.Many efforts have been made by schools to encompass and facilitate youth to promotinghealthy adolescent development. This includes the integration of instilling students with asense of belonging and purpose in life, development a positive self-image and the ability tobecome productive citizens. As educational leaders, we look forward to building aneducational institution where we could have committed leaders and administrators, well -trained teachers, sophisticated curriculums, and adequate facilities and textbooks.Nevertheless, with all these facilitators, what can we expect from schools as a home foryouth development if those young people grow up in families and community characterizedby poverty, violence, lack of health care, high unemployment rates, low-wages, singleparentfamilies, and crime? Under these circumstances, any devotion to school’simprovement without involving simultaneous efforts to address the problems occurred inthe family and community will likely remain undesirable outcomes.